Long-term evaluation of pharyngeal dimensions and hyoid bone position in Class II Malocclusion patients treated with Herbst functional appliance - Marques, Thagid Yasmin Leal Almeida (2021)
Introduction: This study aimed to evaluate the long-term changes in the pharyngeal dimensions and hyoid bone position in Class II malocclusion patients treated with Herbst functional appliance. Methods: The sample was composed of 15 skeletal Class II malocclusion patients (13.00 years old ± 1.21) who had been treated with Herbst functional appliance and followed for a mean period of 10 years (10.73 years ± 3.67). Lateral cephalometric radiographs were used to evaluate the pharyngeal dimensions and hyoid bone position. Radiographic measurements were performed with Dolphin® Imaging 11.9. Intragroup comparison between the evaluation stages was performed with repeated measures ANOVA, followed by Tukey tests if necessary. Results were considered statistically significant at p<0.05. Results: Regarding the pharyngeal variables, only the lower airway space increased significantly in the treatment period and all of them remained stable in the long-term posttreatment period. The hyoid bone moved significantly forward and downward during the treatment period and even further forward during the long-term posttreatment period. Conclusion: The increase in the lower airway space may be related to the forward shift of the mandible plus the growth effect. The hyoid bone was moved forward and downward as a treatment effect. Only the horizontal position of the hyoid bone changed significantly in the long-term posttreatment period, moving forward.